Strategi Peningkatan Mutu Pembelajaran Al-qur’an di Sekolah Menengah Kejuruan An nur Bululawang Malang - Ali Makinudin (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
Many formal schools in Indonesia such as An-NurBululawang Vocational School implemented Al-Qur'an learning programs for students. This school has been implementing Al-Quran learning for years but the learning management still has problems.This study uses a qualitative method with the type of case study research which aims to develop strategies for improving the quality of Al-Qur'an learning. Data analysis uses the Miles and Huberman model, namely data collection, data reduction, data presentation and conclusion drawing and verification. The results of this study indicate that: 1) The steps to improve the quality of Al-Qur'anlearning in Vocational High School An-NurBululawang Malang consist of: a) Planning. b) Implementation. c) Evaluation. d) Follow-up;  2) The implications of improving the quality of Al-Qur'an learning for Vocational High School An-NurBululawang Malang include a) Expansion of the organizational structure. b) Determination of quality standards for Al-Qur'an learning. c) Building the image of the school, and d) Implementation of continuous supervision and evaluation. The previous problem was that the teacher still had difficulty determining the appropriate method. This new strategy makes it easier for teachers to manage Al-Qur'an learning by grouping students according to their respective abilities. This new management strategy improved the quality of Al-Qur'an learning.